Health Education Influences Mother's Knowledge in Preventing Stunting in Infants - Sitorus, Sony Bernike Magdalena; Sasmita, Hanum; Lailatul K., Marlina Fitriya (Jurnal Bidan Cerdas, 2024)
Introduction: The 2022 SSGI results indicate that the prevalence of stunting in Indonesia has decreased from 24.4% to 21.6% compared to the previous year. The target to be achieved by 2024 is to reduce the prevalence of stunting to 14%. Efforts to reduce the incidence of stunting include conducting health promotions about stunting. Purpose: This research aims to analyze the effect of health education on mothers' knowledge about stunting prevention in toddlers in the Malei Health Center working area, Poso Regency. Method: This quasi-experimental study employed a pre-experiment research design with a one-group pretest-posttest approach. The research was conducted in July 2023 in the working area of the Malei Health Center, Lage District, Poso Regency. The sample size was 65 people, selected through simple random sampling. Result: Univariate analysis showed that the majority of respondents were aged 20–35 years (53.9%), had education levels ranging from elementary to junior high school (58.5%), and were unemployed (72.3%). The Wilcoxon test was used for bivariate analysis due to the non-normal distribution of the data. Statistical test results showed a significant increase in respondents' knowledge, with an average score increase of 50.2 and a p-value <0.05. Conclusion: Health education significantly influences maternal knowledge of stunting prevention. It is recommended that health promotion efforts be enhanced through education about stunting.